THE EFFECTS OF CURCUMIN SUPPLEMENTATION ON GLYCAEMIC INDEX IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME: AN EVIDENCE BASED CASE REPORT - Marcia Kumala; Nurul Ratna Mutu Manikam (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2023)
Background: PCOS is the most common cause of infertility around the world. PCOS is associated with impaired glucose tolerance and higher tendency to develop type 2 diabetes. Curcumin, which is known for its anti-inflammatory, antioxidant, and antidiabetic properties, may show promising effect in regulating blood glucose. Objective: This study aims to evaluate the effect of curcumin supplementation on improving glycaemic profile in women with PCOS. Methods: Literature searching was conducted by advanced searching in Pubmed, Cochrane Library, Scopus, and ProQuest database using MeSH Terms combined with Title/Abstract. After removing duplicates, the literatures were screened based on the eligibility criteria. Critical appraisal and level of evidence of the selected literatures were determined based on Oxford Centre for Evidence-Based Medicine. Results: Two selected literatures were relevant to answer our clinical question. The first literature is a systematic review/meta-analysis study by Chien et al (2021) and the latter is a randomized controlled trial by Asan et al (2020). Both literatures show that curcumin supplementation is beneficial in improving glycaemic profile in PCOS patients. These effects were marked by lower fasting blood glucose, insulin level, and HOMA-IR in curcumin group compared to the control group. Conclusion: Curcumin supplementation for at least 6 weeks significantly improve glycaemic profile in women with PCOS. Curcumin supplementation is also considered safe and well tolerable. However, more studies are needed to investigate further regarding the long-term effects of curcumin supplementation. Keywords: curcumin, turmeric, polycystic ovarian syndrome, glycaemic profile